2003
DOI: 10.3763/ijas.2003.0103
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Soil Potassium after Long-Term Organic Dairy Production

Abstract: On five long-term organic dairy farms aiming at selfsufficiency with nutrients, soil concentrations of ammonium-acetate lactate extractable potassium (K-AL) and acid-soluble K was measured twice in topsoil (0-20 cm) and subsoil (20-40 cm) over periods of 6-14 years. Organic management had occurred for Ͼ9 years at the second sampling. On average there were most probably field level K-deficits. Even so, topsoil K-AL concentrations were medium high (65-155 mg K kg ؊1 soil), and did not decrease during the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Møberg and Nielsen (1983) and Nielsen and Møberg (1984), studying K-deficient soils from field crops as well as from pot experiments, reported a trend of reduction in illite content through K depletion, which was accompanied with a corresponding increase in vermiculite or smectite. At the same time, they found that the above changes resulted in respective changes in CEC values, and the above findings were corroborated by Tributh et al (1987) and Løes and Øgaard (2003). Recently, Moterle et al (2016) using X-ray decomposition methods found that the removal of K from the illite interlayers transformed the clay mineral into vermiculite, a fact that had a positive effect on soil exchange capacity.…”
Section: Discussionmentioning
confidence: 74%
“…Møberg and Nielsen (1983) and Nielsen and Møberg (1984), studying K-deficient soils from field crops as well as from pot experiments, reported a trend of reduction in illite content through K depletion, which was accompanied with a corresponding increase in vermiculite or smectite. At the same time, they found that the above changes resulted in respective changes in CEC values, and the above findings were corroborated by Tributh et al (1987) and Løes and Øgaard (2003). Recently, Moterle et al (2016) using X-ray decomposition methods found that the removal of K from the illite interlayers transformed the clay mineral into vermiculite, a fact that had a positive effect on soil exchange capacity.…”
Section: Discussionmentioning
confidence: 74%
“…Nonetheless, there are now some 3 Mha of agricultural land in Europe managed with certified organic practices. Some have led to lower energy use (though lower yields too), others to better nutrient retention and some greater nutrient losses (Dalgaard et al 1998(Dalgaard et al , 2002Løes & Øgaard 2003;Gosling & Shepherd 2004), and some to greater labour absorption Pretty et al 2006).…”
Section: Effects Of Sustainable Agriculture On Yieldsmentioning
confidence: 99%
“…Hypothetically, therefore, K losses and deficiencies are more likely to occur in wet areas than in dry areas because soil erosion, surface runoff, and leaching are greater and cropping is more intense in wet areas. Indeed, excessive mining and deficiency of nutrients like K, which are taken up in large quantities, were reported in continuous cropping systems of the world and where no external inputs had been applied (Loes and Ogaard, 2003;Smaling et al, 1993;Stoorvogel et al, 1993). Nandwa and Bekunda (1998) reported an emergence of such deficiencies in continuously cultivated highlands of east and southern Africa.…”
mentioning
confidence: 97%